The Role Of Brand Trust In Product Quality In Influencing Repurchase Intention For Skintific Products (A Study of Generation Z Consumers) - Tiara Shely Winata; Hadi, Effed Darta (Universitas Muhammadiyah Pontianak, 2026)
This study investigates the relationship between product quality, brand trust, and repurchase intention among Generation Z consumers of Skintific products. Using a quantitative approach, data were collected through an online survey with a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The findings show that product quality positively and significantly influences both brand trust and repurchase intention. Brand trust also partially mediates the relationship between product quality and repurchase intention. These results emphasize the importance of maintaining product quality and strengthening brand trust to encourage customer loyalty. Keywords: Product Quality; Brand Trust; Repurchase Intention